Efeitos da combinação de agrotóxicos glifosato e imidacloprido no desenvolvimento, sistema imunológico e digestório de abelhas Scaptotrigona postica (Latreille, 1807) - Grando, Graziele Campana (2022)
Studies have shown that the decrease in the bee population is associated with multiple factors, with exposure to pesticides being the main factor in Brazil. Thus, the objective of this work was to evaluate the possible effects of residual concentrations of the herbicide glyphosate and the insecticide imidacloprid found, in an isolated and combined form, on the development, the immune system and the digestive system of stingless bees Scaptotrigona postica. For this, in vivo, bioassays were conducted to develop a method to evaluate the toxicity of pesticides in stingless bees. First, we introduced, inside the colony, different materials (wax + parafilm and cerumen) to seal the uncapped brood cells and observed the acceptance of these materials by the bees. In the second and third bioassays, we tested the application of larval food with different types of needles in the brood cells (without uncapping) both in the colony and in the brood disc placed in the incubator. Due to the highly efficient hygienic behavior and the high proliferation of fungi in the brood discs in the incubator, we obtained an emergence index equal to zero, and it was not possible to establish an adequate method for carrying out the in vivo toxicity tests. The development of this method requires deeper studies on the existing micro-ecosystem in the colony and the biology of S. postica. In the second part of the work, we performed in vitro bioassays. S. postica larvae were fed with larval food containing pesticides at the following concentrations: D1 – control (larval food without the addition of active ingredients), D2 – 0.2 ng/µL of glyphosate, D3 – 0.2 ng/µL of imidacloprid and D4 – 0.2 ng/µL of glyphosate + 0.2 ng/µL of imidacloprid and its development was observed until emergence. Biological parameters were evaluated, such as mortality rate, pupation, defecation, and bee emergence. We also evaluated morphometric parameters of head width and intertegular span distance, the immune system's number of cells, and the midgut's histoarchitecture. The data obtained were submitted for statistical analysis using the RStudio software. The results showed that imidacloprid significantly affected the survival rates of the larvae, while the other groups did not change. The morphometry of the intertegular span distance and width of the head was affected by glyphosate, the mixture only showed changes in the measurement of the head and imidacloprid did not show any of the two parameters. There was no change in the number of hemocytes for the larvae exposed to the experimental groups. As for newly emerged bees, exposure to imidacloprid and mixture significantly affected hemocyte density. The results of the midgut's morphological alterations showed organ damage in the experimental groups (D2, D3, and D4). Loss of cytoplasmic material, loss of brush border, and elimination of cells into the lumen were observed. Thus, we conclude that glyphosate can affect the size of individuals and the functioning of the intestine. Imidacloprid can compromise the survival of bees, the immune system of bees, and the digestive system. And finally, the mixture of pesticides did not cause the sum of the effects of the active ingredients but had sublethal effects on the individual's size, the immune system, and the digestive system. The data obtained indicate the need for attention to the risk assessment process of pesticides for bees, including native ones. It also contributes to knowledge about our species of stingless bees.